PENGARUH PENGETAHUAN INVESTASI DAN PERILAKU INVESTOR TERHADAP MINAT INVESTASI DENGAN KUALITAS LAYANAN SEBAGAI VARIABEL MODERASI PADA DINAS PENENAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KABUPATEN KUTAI TIMUR - Murtiningsih; Ausy Riana; Juwita Aprillia; Rizkiawan (Journal Competency of Business, 2026)
This study aims to analyze and explain the effect of Investment Knowledge and Investor Behavior on Investment Intention, with Service Quality as a Moderating Variable at the East Kutai Regency Investment and One-Stop Integrated Service Office. A sample size of 159 respondents was used. The sampling technique used was non-probability sampling. The data analysis used was quantitative using structural equation modeling (SEM). The results of the t-test study show that Investment Knowledge and Investor Behavior have an effect on Service Quality, therefore Ha is accepted and H0 is rejected, Investment Knowledge, Investor Behavior and Service Quality have an effect on Investment Interest, therefore Ha is accepted and H0 is rejected, Service Quality cannot moderate Investment Knowledge and Investor Behavior on Investment Interest, therefore H0 is accepted and H1 is rejected. The first Determination Coefficient obtained from the independent variables (X1 and X2 against Z) in this study is 70.5 percent and the second Determination Coefficient obtained from the independent variables (X1, X2, and Z against Y) in this study is 90.5 percent.